2009
DOI: 10.1074/jbc.m806830200
|View full text |Cite
|
Sign up to set email alerts
|

ABF1-binding Sites Promote Efficient Global Genome Nucleotide Excision Repair

Abstract: Global genome repair (GG-NER) removes DNA damage from non-transcribing DNA. In Saccharomyces cerevisiae, the RAD7 and RAD16 genes are specifically required for GG-NER. We reported that autonomously replicating sequence-binding factor 1 (A BF1) protein forms a stable complex with Rad7 and Rad16 proteins. ABF1 functions in transcription, replication, gene silencing and NER in yeast. We show that binding of ABF1 to its DNA recognition sequence found at multiple genomic locations promotes efficient GG-NER in yeast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 46 publications
7
23
0
Order By: Relevance
“…We have reported that binding of the Abf1 component of the GG-NER complex to one of its DNA recognition sequences promotes efficient GG-NER both in vitro and in vivo (Yu et al 2009). Using standard chromatin immunoprecipitation (ChIP) and qPCR, we demonstrated Abf1 binding at a single Abf1 consensus binding site called the "I silencer," located at the yeast HMLALPHA locus (Yu et al 2009). Mutation of this DNA consensus site caused loss of Abf1 and GG-NER complex binding and reduced GG-NER efficiency extending from the mutated Abf1 DNA binding site.…”
Section: Gg-ner Is Organized and Initiated From Abf1 Binding Sites Fomentioning
confidence: 99%
See 2 more Smart Citations
“…We have reported that binding of the Abf1 component of the GG-NER complex to one of its DNA recognition sequences promotes efficient GG-NER both in vitro and in vivo (Yu et al 2009). Using standard chromatin immunoprecipitation (ChIP) and qPCR, we demonstrated Abf1 binding at a single Abf1 consensus binding site called the "I silencer," located at the yeast HMLALPHA locus (Yu et al 2009). Mutation of this DNA consensus site caused loss of Abf1 and GG-NER complex binding and reduced GG-NER efficiency extending from the mutated Abf1 DNA binding site.…”
Section: Gg-ner Is Organized and Initiated From Abf1 Binding Sites Fomentioning
confidence: 99%
“…Abf1 has a wide range of functions in processes including transcription (Buchman et al 1988;Miyake et al 2004;Yarragudi et al 2007;Schlecht et al 2008), gene silencing (Boscheron et al 1996;Zou et al 2006;Zhang et al 2012), replication (Rhode et al 1992), and NER (Yu et al 2004(Yu et al , 2009). We have reported that binding of the Abf1 component of the GG-NER complex to one of its DNA recognition sequences promotes efficient GG-NER both in vitro and in vivo (Yu et al 2009).…”
Section: Gg-ner Is Organized and Initiated From Abf1 Binding Sites Fomentioning
confidence: 99%
See 1 more Smart Citation
“…Rad7-Rad16-Abf1 can generate superhelical torsion in DNA in vitro (Yu et al 2004), suggesting a model in which the complex binds to ABF1 sites in DNA in the absence of UV irradiation. Following UV irradiation, the complex uses ATP hydrolysis to translocate on DNA, generating conformational changes and eventually stalling at damaged sites to facilitate the recruitment of Rad4 (Guzder et al 1998;Yu et al 2009). …”
Section: ; Tremblay Et Al 2008)mentioning
confidence: 99%
“…1,9 This relatively simple picture has been recently expanded by a study showing that most Ribi gene promoters are demarcated, at positions ranging from 250 to 50 bp upstream of PAC and RRPE, by one or more binding sites for the GRFs Abf1, Reb1, Tbf1 and Rap1. 15 All of these proteins possess a Myb-like DNA-binding domain, bind to several hundreds of promoter regions in the S. cerevisiae genome and are multifunctional, being involved in processes other than transcription initiation, such as DNA repair, 16,17 telomere regulation, 18,19 and transcription termination. 20 The observation that all the yeast regulons involved in rRNA maturation and ribosome production (including snoRNA genes in addition to RP and Ribi genes 21 ) share GRF-associated promoters raises questions about the physiologic significance of these transcription factors in regulon modulation according to cell growth conditions.…”
mentioning
confidence: 99%